2011
DOI: 10.1177/0748730411419775
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Phase Shifts the Rhythmic Expression of PERIOD2::LUCIFERASE

Abstract: Valproic acid (VPA) is an anticonvulsant used to treat bipolar disorder, a psychiatric disease associated with disturbances in circadian rhythmicity. Little is known about how VPA affects circadian rhythms. The authors cultured tissues containing the master brain pacemaker for circadian rhythmicity, the suprachiasmatic nuclei (SCN), and skin fibroblasts from transgenic PERIOD2::LUCIFERASE (PER2::LUC) mice and studied the effect of VPA on the circadian PER2::LUC rhythm by measuring bioluminescence. VPA (1 mM) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 46 publications
5
74
0
Order By: Relevance
“…Previous work has shown that VPA shifts the phase and increases amplitude of PER2 rhythms in cultured SCN explants and fibroblasts (Johansson et al, 2011). In hamsters, low concentrations of VPA had no effect on circadian period (Klemfuss and Kripke, 1995).…”
Section: Discussionmentioning
confidence: 72%
“…Previous work has shown that VPA shifts the phase and increases amplitude of PER2 rhythms in cultured SCN explants and fibroblasts (Johansson et al, 2011). In hamsters, low concentrations of VPA had no effect on circadian period (Klemfuss and Kripke, 1995).…”
Section: Discussionmentioning
confidence: 72%
“…It has been demonstrated that it can also affect circadian rhythms. Valproic Acid, in different circadian timings, can alter the phase (delay or advance) and increase the amplitude of Per2 gene rhythm (Johansson, Brask et al 2011).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…The mood stabilizer valproic acid shifts phase and increases amplitude of clock gene expression rhythms in SCN and fibroblasts [118], but it has less consistent effects on circadian period compared to lithium [119]. It also influences the expression of several circadian genes in the amigdala [120].…”
Section: Valproic Acidmentioning
confidence: 99%